New Therapeutic Aspects of Inflammatory Cardiomyopathy - Kuchynka, Petr; Palecek, Tomas; Nemecek, Eduard; Fikrle, Michal; Linhart, Ales (Current Pharmaceutical Design, 2015)
Inflammatory cardiomyopathy is a term used for left ventricular systolic dysfunction associated with myocarditis. In order to establish definitely the diagnosis, an endomyocardial biopsy (EMB) must be performed. Based on the results of EMB analysis, specific treatment may be added to conventional heart failure therapy. Immunosuppressive therapy in patients with non-viral inflammatory cardiomyopathy has been shown to be effective, and there is also some evidence that antiviral or antimicrobial therapy may be beneficial.
Keywords: antimicrobial treatment